Pengaruh Gaya Kepemimpinan dan Komunikasi Terhadap Kinerja Pegawai di Gudang Distributor PT. Bina San Prima Tasikmalaya - Barin Barlian (LPPM AMIK Citra Buana Indonesia, 2017)
The purpose of this study is: to know Style Leadership, Communication and Employee Performance at Branch Mc'Donalds Tasikmalaya, to determine the effect on the Performance Leadership Style, effect and influence on the Performance Communication Leadership Style and communication together (simultaneously) on the Performance of the Mc 'Donalds Branch Tasikmalaya. Author of the research methods used in this research is descriptive and associative. Unit analysis on Warehouse Distributors Warehouse employee PT. Bina San Prima Tasikmalaya many as 31 people. The conclusion of this study is as follows. Leadership Styles on Employees PT. Bina San Prima included in the category of Pretty Good with scores of 92, but there are still below average in the dimensions of autocratic leadership. Communication on employees of PT. Bina San Prima included in the category of Pretty Good with scores of 92, but there are still below the average the dimensions Communications Diagonal. Employee Performance PT. Bina San Prima included in the category of Pretty Good with scores of 92, but there are still below average in the dimensions of quality. Leadership style influence on Employee Performance at PT. Bina San Prima at 0.2202 so H0 is rejected and HI accepted (accepted hypothesis). Communications effect on Employee Performance at PT. Bina San Prima at 0.2515 H0 and HI accepted (the hypothesis is accepted) .. 6). There is the influence of leadership style and communication together (simultaneously) on Employee Performance at PT. Bina San Prima at 0.472